Preoperative risk factors of airway complications in adult lung transplant recipients: A systematic review and meta-analysis - Subaşı, Mahmut; Düger, Mustafa (Baycinar Medical Publishing, 2023)
Background: In this systematic review and meta-analysis, we aimed to identify recipient-related preoperative risk factors for airway complications following lung transplantation in adults. Methods: Articles published between November 1995 and February 2023 were searched by a thorough exploration of databases. Studies that addressed recipient-related risk factors for airway complications following adult lung transplantation, such as cohorts, case-control, or cross-sectional studies, were included. Fixed-effects or random-effects models were used to calculate the odds ratios (ORs) or mean differences (MDs) with 95% confidence interval (CI). Results: Twenty-one studies including a total of 38,321 recipients fulfilled the inclusion criteria. Based on the pooled analyses, taller height (MD=5.98, 95% CI: 5.69-6.27, I2 = 57.32%), intraoperative mechanical ventilation (OR=1.83, 95% CI: 1.41-2.38, I2=0%), male sex (OR=1.52, 95% CI: 1.33-1.74, I2=15.91%), preoperative extracorporeal membrane oxygenation (OR=1.58, 95% CI: 1.1-2.26, I2 =41.47 %), and preoperative steroid use (OR=1.21, 95% CI: 1.04-1.41, I2 = 0%) elevated the risk of airway complications following lung transplantation. Conclusion: Taller height, intraoperative mechanical ventilation, male sex, preoperative extracorporeal membrane oxygenation, and preoperative steroid use can increase the risk of airway complications after lung transplantation. Identifying high-risk recipients or riskless situations can support the advancement of selective treatments or prevent the unnecessary avoidance of certain interventions.

Amaç: Bu sistematik derleme ve meta-analizde, erişkinlerde akciğer nakli sonrasında hava yolu komplikasyonlarının alıcı ile ilişkili ameliyat öncesi risk faktörleri belirlendi. Çalışma planı: Kasım 1995 - Şubat 2023 tarihleri arasında yayımlanan makaleler kapsamlı bir veri tabanı araştırması ile tarandı. Kohortlar, vaka kontrol veya kesitsel çalışmalar gibi erişkin akciğer naklini takiben hava yolu komplikasyonları için alıcı ile ilişkili risk faktörlerini değerlendiren çalışmalar dahil edildi. %95 güven aralığı (CI) ile birlikte olasılık oranlarını (OR) veya ortalama farklarını (MD) hesaplamak için sabit etki veya rastgele etki modelleri kullanıldı. Bulgular: Toplam 38.321 alıcının yer aldığı 21 çalışma dahil edilme kriterlerini karşıladı. Birleştirilmiş analizlere göre uzun boy (MD=5.98, %95 CI: 5.69-6.27, I2=%57.32), ameliyat sırası mekanik ventilasyon (OR=1.83, %95 CI: 1.41-2.38, I2 =%0), erkek cinsiyeti (OR=1.52, %95 CI: 1.33-1.74, I2 =%15.91), ameliyat öncesi ekstrakorporal membran oksijenizasyonu (OR=1.58, %95 CI: 1.1-2.26, I2=%41.47) ve ameliyat öncesi steroid kullanımı (OR=1.21, %95 CI: 1.04-1.41, I2=%0) akciğer nakli sonrası hava yolu komplikasyon riskini artırdı. Sonuç: Uzun boy, ameliyat sırası mekanik ventilasyon, erkek cinsiyeti, ameliyat öncesi ekstrakorporal membran oksijenizasyonu ve ameliyat öncesi steroid kullanımı akciğer nakli sonrası hava yolu komplikasyon riskini artırabilir. Yüksek riskli alıcıları veya hava yolu komplikasyon riskini artırmayan durumları belirlemek, selektif tedavilerin seçimini destekleyebilir veya belirli girişimlerden gereksiz yere kaçınmayı önleyebilir.
Erişkin akciğer nakli alıcılarında hava yolu komplikasyonlarının ameliyat öncesi risk faktörleri: Sistematik derleme ve meta-analiz
Keywords: Airway Complications; Lung Transplantation; Risk Factors; Hava Yolu Komplikasyonları; Akciğer Nakli; Risk Faktörleri